MENTAL PATTERNS ACCORDING TO THE AVEM TEST OF THE VIENNA SYSTEM AND ITS RELATIONSHIP TO THE PERFORMANCE OF SOME PHYSICAL ABILITIES OF FOOTBALL PLAYERS - Dr. Saba Shaker Farhan; Dr. Raafat Abdul Hadi Al-Krwoy (Proximus Journal Publishing, 2024)
The research included the introduction and the importance of the research: It addressed the importance of the physical aspect of football players, as well as the importance of identifying the variables that affect the physical aspect of football. The research problem was to identify the nature of the relationship between the mental pattern and the physical abilities of football players due to the lack of information about this relationship in the sources according to the researchers' knowledge. The aim of the research is to identify the nature of the relationship between the mental pattern and the physical abilities of football players.
Keywords: Mental styles; AVEM test; Vienna test system; Physical abilities